001.6 Exploring the benefits of molecular testing for gonorrhoea antibiotic resistance surveillance in remote settings. (13th September 2015) - Hui, B; Ryder, N; Su, J-Y; Ward, J; Chen, M; Donovan, B; Fairley, C; Guy, R; Lahra, M; Law, M; Whiley, D; Regan, D
Abstract : Background: The latest nucleic acid amplification tests (NAAT) for gonorrhoea are convenient and accurate, and are often used in place of culture-based tests for diagnosis. However the increasing use of NAATs in remote settings in Australia has compromised surveillance for gonorrhoea antimicrobial resistance (AMR). A molecular resistance test that can make use of samples collected for NAAT diagnosis may provide a means to enhance surveillance in remote settings where the availability of samples suitable for culture-based AMR testing is declining. We used a mathematical model to assess the potential benefit of a molecular test in terms of the timeliness of detection of gonorrhoea AMR. Methods: An individual-based mathematical model was developed to describe the transmission of gonorrhoea in a remote Indigenous population in Australia. We estimated the impact of the molecular test on the time delay between first importation and the first confirmation that the prevalence of gonorrhoea AMR has breached the WHO-recommended 5% threshold (when a change in antibiotic should occur). Results: The model suggests that when culture is the only means of testing for AMR, the breach will only be detected when the actual prevalence of AMR in the population has already reached 8 – 18%. With the addition of a molecular AMR test and assuming AMR can be determined for all samples, the breach will be detected when the actual prevalence of AMR in the population has reached 6%, which only slightly exceeds the recommended notification threshold of 5%. Conclusion: Molecular tests have the potential to provide more timely warning of the emergence of gonorrhoea AMR in remote settings where surveillance is compromised by the increased use of NAATs for diagnosis. This in turn will facilitate earlier treatment switching and more targeted treatment, which has the potential to reduce the population impact of gonorrhoea AMR. Disclosure of interest statement: This work was supported by National Health and Medical Research Council Project Grants (APP1025517). The National Neisseria Network is funded by the Australian Government Department of Health. The Kirby Institute is funded by the Australian Government Department of Health and Ageing and is affiliated with the Faculty of Medicine, University of New South Wales. The views expressed in this publication do not necessarily represent the position of the Australian Government.